2020
DOI: 10.19184/jsep.v13i3.20281
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency of Paddy’s Farming in Various Types of Paddy’s Seeds in Indonesia

Abstract: The increasing need for food along with increasing population is one of the problems that must be resolved by Indonesia nation. The government is trying to increase rice production and productivity by using certified seeds. Certified seeds is expected to affect technical efficiency of rice farming. The objectives of this studies are to analyze the level of technical efficiency and to identify the factors that influence the technical efficiency of rice farming in various types of main sources of rice seeds in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…It can be interpreted that an increase in the use of seeds by one percent will reduce production by one percent. This result is in line with previous research conducted by [51,53]. However, these results contradicted another research, which concluded that a certain, good method or procedural seeding could increase production [44].…”
Section: Analytical Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…It can be interpreted that an increase in the use of seeds by one percent will reduce production by one percent. This result is in line with previous research conducted by [51,53]. However, these results contradicted another research, which concluded that a certain, good method or procedural seeding could increase production [44].…”
Section: Analytical Resultssupporting
confidence: 90%
“…The chemical manure variable had a significant positive effect on production, indicating that a one-percent increase in fertilizer will increase production by one percent. The estimation result is confirmed by the result of [43,[47][48][49][50][51][52][53]. The estimation results suggested that rice farmers have used the optimal amount of chemical manure as an input.…”
Section: Analytical Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Moreover, one of the essential characteristics of econometric models (SFA) is that it allows a specification for panel data and the construction of confidence intervals [41]. Several previous studies in various countries used SFA to assess the TE level of rice farming [19,22,25,27,28,30,32,34,[42][43][44].…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Enhancing TE is a crucial factor in stimulating productivity, and thus, studying TE is integral to evaluating farming efficiency and identifying methods to augment productivity, ultimately achieving optimal conditions. Numerous studies have been conducted on TE of rice farming and its determinants in various locations in Indonesia [18][19][20][21][22][23], Asia [24][25][26][27][28][29][30][31], and Africa [32][33][34][35], employing diverse approaches/methods. Despite the abundance of studies on TE in rice farming, the focus has primarily been on irrigated and rainfed rice farms, while studies on tidal swamp areas remain limited.…”
Section: Introductionmentioning
confidence: 99%